2021
DOI: 10.1149/1945-7111/ac1cc6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of N-Type CuGaS2 Nanoparticles and Films for Purpose of Photoelectrocatalytic Water Splitting

Abstract: In this work, n-type CuGaS2 (CGS) nanoparticles were synthesized using an original colloidal method in N-Methylimidazole solvent with GaCl3, Li2S and CuCl as Ga3+, S2− and Cu+ precursors, respectively. After annealing at 600 °C, energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy revealed an excess of gallium with a bulk Ga/Cu atomic ratio of 1.01 and a larger value at the surface. The CGS X-ray diffraction pattern is compatible with a chalcopyrite crystalline phase with crystallites size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…At present, there is little research on photo-electric coenzyme regeneration based on microreactors, but the research on water decomposition based on microreactors is expected to promote its future progress. It is found that the oxidative decomposition of water can be realized by PEC [ 159 , 160 ], and holes can be trapped only by water as an electron sacrificial agent in this system [ 161 , 162 ], which effectively reduces the reverse transfer of electrons and helps to realize environmentally friendly, efficient, and economical photo-electric catalytic coenzyme regeneration without additional high-value amines as electron sacrificial agents [ 163 ]. Thakur et al reported that they successfully prepared a paper-based photo-anode (PA) with good flexibility and stability by depositing polypyrrole (PPy) with electrical conductivity, high solar energy absorption, and a suitable cross-band (water oxidation–reduction) on laboratory filter paper, which produced a photocurrent density of about 9.5 mA/cm 2 (1.23 V vs. RHE) in a three-electrode system ( Figure 8 E), and realized efficient and stable photo-electrochemical water decomposition [ 154 ] He et al reported a metal–organic framework with an assembled bifunctional microreactor ( Figure 8 F).…”
Section: Coenzyme Regeneration In Conventional System and Microreacto...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is little research on photo-electric coenzyme regeneration based on microreactors, but the research on water decomposition based on microreactors is expected to promote its future progress. It is found that the oxidative decomposition of water can be realized by PEC [ 159 , 160 ], and holes can be trapped only by water as an electron sacrificial agent in this system [ 161 , 162 ], which effectively reduces the reverse transfer of electrons and helps to realize environmentally friendly, efficient, and economical photo-electric catalytic coenzyme regeneration without additional high-value amines as electron sacrificial agents [ 163 ]. Thakur et al reported that they successfully prepared a paper-based photo-anode (PA) with good flexibility and stability by depositing polypyrrole (PPy) with electrical conductivity, high solar energy absorption, and a suitable cross-band (water oxidation–reduction) on laboratory filter paper, which produced a photocurrent density of about 9.5 mA/cm 2 (1.23 V vs. RHE) in a three-electrode system ( Figure 8 E), and realized efficient and stable photo-electrochemical water decomposition [ 154 ] He et al reported a metal–organic framework with an assembled bifunctional microreactor ( Figure 8 F).…”
Section: Coenzyme Regeneration In Conventional System and Microreacto...mentioning
confidence: 99%
“…At present, there is little research on photo tric coenzyme regeneration based on microreactors, but the research on water deco sition based on microreactors is expected to promote its future progress. It is found the oxidative decomposition of water can be realized by PEC [159,160], and holes c trapped only by water as an electron sacrificial agent in this system [161,162], which tively reduces the reverse transfer of electrons and helps to realize environmen friendly, efficient, and economical photo-electric catalytic coenzyme regeneration wi Compared with the conventional system, photo-electric catalytic coenzyme regeneration based on a microreactor has the advantages of easy recovery of catalytic materials, high product purity, and high efficiency. At present, there is little research on photo-electric coenzyme regeneration based on microreactors, but the research on water decomposition based on microreactors is expected to promote its future progress.…”
Section: Photo-electrocatalysis Coenzyme Regenerationmentioning
confidence: 99%
“…photocatalysis, light-emitting diodes, solar cells, etc., were limited for practical applications owing to their toxicity. This led to a surge in research for finding an alternative environmentally benign semiconductor material with reasonable efficiency compared to that of heavy-metal-based materials. Recently, I–III–VI 2 ternary semiconductors have attracted much interest due to their narrow band gap, high stability against radiation, low cost, tunable emission wavelength, and high optical absorption coefficient. , Among the various Cu-based ternary chalcogenides, CuGaS 2 is greatly studied as a visible light photocatalyst, a light-emitting diode, and a host material in intermediate-band solar cells due to its low toxicity, good stability, and excellent electrical and optical properties. A direct band gap value of 2.4 eV makes it an efficient catalyst in the field of visible light photocatalyst applications. Based on the arrangement of cations in the crystal lattice, it is known to exist in three polymorphic states, viz.…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 Recently, I–III–VI 2 ternary semiconductors have attracted much interest due to their narrow band gap, high stability against radiation, low cost, tunable emission wavelength, and high optical absorption coefficient. 4 , 5 Among the various Cu-based ternary chalcogenides, CuGaS 2 is greatly studied as a visible light photocatalyst, a light-emitting diode, and a host material in intermediate-band solar cells due to its low toxicity, good stability, and excellent electrical and optical properties. A direct band gap value of 2.4 eV makes it an efficient catalyst in the field of visible light photocatalyst applications.…”
Section: Introductionmentioning
confidence: 99%